(untitled) (Eurasian Journal of Humanities and Social Sciences, 2024)
The article examines the key measures undertaken by Uzbekistan to combat poverty and improve the living conditions of its citizens. Data indicates a significant reduction in the poverty rate from 17% in 2021 to 11% in 2023. Successful initiatives are described, such as the "Mahallabay" system, the implementation of preferential loans and subsidies for entrepreneurs, as well as programs for providing land plots to low-income families. The necessity of a comprehensive approach is emphasized, including education, employment, and infrastructure development. The "From Poverty to Prosperity" program focuses on individual support strategies for those in need and the creation of new jobs.